2019
DOI: 10.1155/2019/1401894
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-Like Receptors (TLR2 and TLR4) in the Eyes of Mice with Disseminated Acanthamoebiasis

Abstract: Toll-like receptors (TLRs) play a key role in the innate immune response to numerous pathogens, including Acanthamoeba spp. The aim of this study was to determine the expression of TLR2 and TLR4 in the eyes of mice following intranasal infection with Acanthamoeba spp. in relation to the host’s immunological status. Amoebae used in this study were isolated from the bronchial aspirate of a patient with acute myeloid leukemia (AML) and atypical symptoms of pneumonia. We found statistically significant differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Our previous study has shown that the infection of an eye may also take place via the migration of trophozoites through the optic nerve from the brain to the eyes [14]. Moreover, we observed an altered expression of Toll-like receptors (TLR) 2 and 4 in the eyes of mice intranasally infected with Acanthamoeba spp.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Our previous study has shown that the infection of an eye may also take place via the migration of trophozoites through the optic nerve from the brain to the eyes [14]. Moreover, we observed an altered expression of Toll-like receptors (TLR) 2 and 4 in the eyes of mice intranasally infected with Acanthamoeba spp.…”
Section: Introductionmentioning
confidence: 85%
“…In this study, a continuation of our previous study [14], we want to show that the dysregulation of antioxidants is a part of the pathomechanism during acanthamoebiasis. Therefore, we analyzed the activity of enzymatic antioxidants and the concentration of non-enzymatic antioxidant in the eyes of Acanthamoeba-infected immunocompetent and immunocompromised mice.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations